Cutting performance of different coatings during minimum quantity lubricant milling of AA6061T6 - Mohd Khairil Hafizi, Khairolazar (2013)
This report presents an experimental investigation on the effects of output parameters which are surface roughness, tool wear and material removal rate during machining aluminum alloy 6061-T6 using minimum quantity lubricant (MQL) technique. The minimum quantity of lubrication technique was becoming increasingly more popular due to the safety of environment. The cutting speed, depth of cut, feed rate and MQL flow rate were selected input parameters in this study. This experiment was conducted based on central composite design (CCD) method. To develop a model of process optimization based on the response surface method. MQL parameters include nozzle direction in relation to feed direction, nozzle elevation angle, distance from the nozzle tip to the cutting zone, lubricant flow rate and air pressure. To achieve a maximum output parameters based on the optimized process parameters for coated carbide cutting tools (CTP 2235). The surface roughness was increased with decrease of cutting speed. The optimum cutting condition for MQL and flooded are obtained. For MQL, the feed rate, depth of cut, cutting speed and MQL flow rate are 379 (mm/tooth), 2 (mm), 5548.258 (rpm) and 0.333 (ml/min) respectively. For flooded, the feed rate, depth of cut, cutting speed and MQL flow rate are 379 (mm/tooth), 2 (mm) and 5563.299 (rpm) respectively. It was seen that a majority of coated carbide inserts had a long tool wear when exposed to high cutting speed, and feed rate leading to breakage of the inserts.